The status of assisted reproductive technology in the public health sector in Africa – a multi-country survey - Majangara, Karaga Rumbidzai (Department of Obstetrics and Gynaecology, 2023)
Introduction: It was presumed that most Assisted Reproductive Technology (ART) centres in Africa existed in the private sector. Over 80% of the South African population accessed medical care at public rather than private institutions; hence availability of a health service in both private and public institutions would ensure equitable access to care. Objectives: To determine the availability and utilisation of ART services in the public sector in African countries; and the facilitators and barriers towards service provision. Methods: A mixed methods internet-based cross sectional survey was conducted in Africa in 2 phases. Countries providing ART in Africa were identified from the African Network and Registry of ART (ANARA) database and International Federation of Fertility Societies (IFFS) surveillance report 2019. For phase 1, purposeful sampling of key informants (leaders of fertility societies; contributors to ANARA and IFFS report) was done. Phase 1 participants identified and referred participants for Phase 2, ie- a fertility expert (clinician/ embryologist/ nurse) currently providing ART or previously involved in the establishment or running of a public ART centre. Data were collected via a mostly structured questionnaire (phase one); and semi-structured questionnaire followed by an interview via zoom or WhatsApp calling (phase 2). Data were analysed descriptively based on the principles of grounded theory for qualitative research. Results: Phase 1: participants from 17/27 (63.0%) countries known to provide ART responded. Data for South Africa were obtained from the South African Registry of ART (2019). Public sector ART was available in 10/18 participating countries (55.6%) and 10/16 (62.5%) countries that provided ART. Few of the reported African ART centres were public 24/185 (13.0%). Utilisation of ART was low, < 500 ART cycles per annum, in 13/15 public centres where utilisation was reported. Phase 2: Questionnaires were returned from 6/10 (60%) countries with public ART services and 13/24 (54.2%) identified public ART centres. 8 interviews were done; Nigeria (4), SA (2), Tunisia (1), and Benin (1). Centres mostly agreed there had been local research showing a high burden of infertility requiring ART and the need to help couples that could only access health care in public centres. Patient eligibility criteria for access to ART were utilised variably by 10/13 public centres. The government/ university hospital heavily subsidised ART. Out of pocket co-payments were unavoidable in all centres. The number of ART cycles per annum appeared inversely correlated to the co-payment. The top 3 barriers to ART in the public sector were lack of policy/ legislation; high costs; and bureaucracy. The top 3 measures to promote access to public ART were government buy in, minimising costs and minimising bureaucracy. Conclusion: Public ART services were available in Africa, but restricted and riddled by many challenges. Funding was the biggest challenge. Adopting measures that reduced copayments was associated with higher utilisation of services.